Atmospheric Dynamics Analysis of Extreme Rain Events Using Radiosonde Observation Method (Case Study of Extreme Rain for The Period Of 21-31 March 2024 in Probolinggo (Paiton), East Java - Zaky Aidhil Azzikry; Eva Darnila (Yayasan Kita Menulis - JoCPES, 2024)
Rain extreme is one of phenomenon weather extreme that can cause disaster like flood and land landslide. Understanding about dynamics the atmosphere that causes the occurrence Rain extremes are very important to predict and anticipate possibility the occurrence disaster This study aims to analyze dynamics the atmosphere that causes incident Rain extreme in Probolinggo (Paiton), East Java in the period 21-31 March 2024 using method radiosonde observations. Research methods used covered rainfall data collection Rain daily, radiosonde data (temperature, humidity, wind), and real data from the numerical model global weather / climate. Data analysis was carried out using method statistics, visualization of skew-T log-P diagrams, analysis pattern wind, distribution humidity, convergence / divergence, and analysis dynamics atmosphere use equality movement and continuity. Expected results from This research is better understanding deep about dynamics the atmosphere that causes Rain extremes in the study area, such as pattern circulation wind, source water vapor, lifting processes, and mechanisms formation Rain extreme. This research can also give contribution in development system warning early and mitigation disaster related Rain extreme in the study area and other areas with similar characteristics.